Di-n-butyl-ammonium 2-(3,5-di-tert-butyl-4-hydroxy-benzyl-sulfan-yl)nicotinate - Mansor, S.; Yehye, Wageeh Abdulhadi; Ariffin, A.; Abd Rahman, Noorsaadah; Ng, Seik Weng (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(8)H(20)N(+)·C(21)H(26)NO(3)S(-), contains two indpendent ion pairs which are disposed about a psuedo-inversion center, generating an ammonium-carboxylate N-H⋯O hydrogen-bonded four-component cluster. In the crystal structure, adjacent clusters are linked by hydr-oxy-carboxylate O-H⋯O hydrogen bonds, forming a chain.